Human auditory evoked gamma-band magnetic fields. - Pantev, C (1991)
We have discovered a ca. 40-Hz transient magnetic oscillatory response, evoked in the human brain by the onset of auditory stimuli, consisting of four or more cycles locked in phase to stimulus onset in approximately the 20- to 130-ms poststimulus interval. The response originates in the supratemporal auditory cortex, some millimeters deeper and anterior to the source of the larger-amplitude slow-wave M100 component of the evoked magnetic field and moves in a posterior arcing trajectory 1 cm or more in length. The oscillatory cortical activation elicited by auditory stimuli may be similar to the gamma-band cortical oscillations elicited by olfactory and visual stimuli and may represent an essential component of auditory perceptual processing.